An Analysis of the Second Year Students’ Barriers in Listening Comprehension at SMP N 12 Padang - Rani Dade Augustin; Edi Trisno (Journal of English Language Teaching, 2021)
This research belongs to descriptive research. Based on the English syllabus of curriculum 2013 for Junior High School, most basic competencies are concerning listening and reading skills. For transactional and interpersonal texts, listening competencies are dominant. Furthermore, many students have lower concentration during listening. Students assumed that it is difficult to comprehend the point of the speaker. The educator has a responsibility to know and solve the obstacles faced by students. This research aims to find out the barriers to students listening comprehension. The subject of this research was the second-year students of SMP N 12 Padang. In this case, the writer takes 20% of the population sampling. They were 66 students. There were two research instruments used to obtain the data along with this study. Those were questionnaires and interviews. The questionnaire was used to identify the barriers of the students while the interview was used to make sure the proof of the questionnaire. In analyzing the data, the writer used the descriptive quantitative technique with percentage, as formulated below:P =  × 100 %Based on the data analysis, the students' barriers in listening comprehension were related to two factors. They were external barriers and internal barriers. The external barriers faced by students are the quality of the recording, temperature of the classroom, speaker accents, speaker speed, noises around, and unfamiliar words. While, internal barriers faced by students are anxiety, boredom, unable to concentrate, and loss of focus.